Acacia melanoxylon in Argentina: heartwood content and its relationship with site, growth and age of the trees - Igartúa, Dora-Virginia; Moreno, Karen; Monteoliva, Silvia-Estela (Forest Systems, 2017)
Aims of study: To characterize the wood of Acacia melanoxylon in relation to its potential use in the construction and furniture industry, here we determined the heartwood and sapwood content and distribution within the stem and analyzed their relationship with the growing site, age and growth rate of the trees. Finally, we predicted heartwood content by two easy-to-measure variables. Area of study: Buenos Aires, Argentina. Methods: 20 trees aged between 9 and 32 years were sampled in four sites. Axial sampling was carried out at four heights of the stem (base, breast height, and 30% and 50% of the total height), and the heartwood content (percentage and volume) and sapwood content (cm) determined. Results: The trees analyzed presented conical-shaped heartwood following the outline of the stem along all its commercial height. Within the stem, the highest volume of heartwood was observed at the basal region (53%) and up to 30% of total height, a feature observed in all the sites studied. The sapwood content was constant along the entire stem (2.18 cm). The age of the trees did not influence the heartwood content, whereas the environmental conditions provided by each site (heartwood/volume and heartwood/diameter growth positive ratios) did affect this feature. Research highlights: The absolute amount of heartwood was driven by growth rate, due to the forest structure of non-uniform age. The heartwood volume can be estimated through fitting linear equations (R2 0.78 - 0.89) with two easily measurable variables such as diameter at breast height and tree height.